Modification of silk fibroin film structure: From silkworm diet to material properties - Kaewpirom, Supranee; Teangtam, Watcharin; Monthatong, Monthira; Boonsang, Siridech (My University, 2025)
This study investigates the structural modification of silk fibroin films through dietary supplementation of Bombyx mori silkworms with probiotics (lived L. pentosus SF66) and paraprobiotics (heat-killed L. pentosus SF66). Physical appearance, tensile properties, and morphology of reeled silk fibers were characterized. Fibers were purified and dialyzed to obtain aqueous silk fibroin solutions, which were cast into regenerated films (CON-F, PRO[sbnd]F, and PARA-F). Dietary supplementation influenced the film-forming properties of silk fibroin. Fourier-transform infrared spectroscopy and wide-angle X-ray diffraction analyses revealed that crystallinity decreased in the order CON-F > PARA-F > PRO-F, corresponding to reduced β-sheet content and increased random coil conformations. Both probiotic and paraprobiotic supplementation demonstrated mechanisms for modulating silk fibroin conformational transitions and structural organization. Real-time polymerase chain reaction analysis of key silk fibroin genes (fibroin heavy chain, fibroin light chain (fib-l), and 25-kD polypeptide protein) demonstrated elevated expression in the paraprobiotic-supplemented group, with fib-l showing the most pronounced upregulation. A mechanistic model explaining how these nutritional interventions affect silk film formation is proposed. These findings provide insights for developing targeted nutritional strategies to modify the secondary protein structure of regenerated silk films.
Keywords: Probiotic/paraprobiotic supplementation; Protein secondary structure; Silk fibroin film